Comparative analysis of sexual selective traits in Giant Hissing Cockroaches (Tribe: Gromphadorhini) - Tessa, Amy (2020)
Through male competition and female choice, sexual selection favours traits that are advantageous for mating success. Trait investment is costly; therefore, males invest a set amount of resources into pre-copulatory traits to aid in competition or post-copulatory traits to increase fertilisation success. The aim of this project was to investigate hissing cockroach sexual selection, looking at both female choice and post-copulatory sperm competition. Firstly, by manipulating horn length of models in two-way choice experiments to understand what role weaponry might play in competition and female choice, in both Gromphadorhina oblongonota and Aeluropoda insignis species. Secondly, by comparing post-copulatory traits and horn size across five hissing cockroach species to understand investment allocation and sperm competition pressures. Both G. oblongonota and A. insignis were able to distinguish between control and life-like models. However, when using life-like models with manipulated weaponry, females and males displayed no preference towards horn length. Horns are likely one part of a complex multi-modal signal in male-male interactions and females may not choose males based on this pre-copulatory trait. Comparing post-copulatory traits between the five species, A. insignis, G. oblongonota and Elliptorhina javanica differed significantly in horn length, relative testes mass, spermatophore weight, sperm number, acrosome and head length. However, these species are phylogenetically distant from one another, which could play a large role in driving their trait differences. Comparing sperm morphology and other post copulatory traits, similar patterns in trait investment were found and relationships often became non-existent when correcting for phylogenetic relatedness, suggesting these species may have similar levels of post-copulatory sperm competition. Due to sexual selection pressures being species specific, intraspecific patterns might be more revealing about response to local selection pressure rather than generic pressure amongst species as different species may respond to this shared pressure in different ways. These results imply a complex influence of phylogenetic dependence and sexual selection pressures on post copulatory traits, similar to other studies that correct for phylogenetic relatedness.